The Experiences and Meanings of Nurses’ Smiles to Patients in the Emergency Department - Fitriana, Vera; Santoso, Agus; Dharmana, Edi (Nurse Media Journal of Nursing, 2021)
Background: Psycho-emotional aspects play an important role in both health services and health workers in the emergency department. Smiles are forms of interactions between nurses and patients that are given in providing health services to patients in terms of nonverbal communication. However, high workloads in the emergency unit may hinder nurses from smiling. Purpose: This study aimed to explore the experiences and meanings of nurses’ smiles to patients in the emergency department.Methods: This study employed a qualitative design with a descriptive phenomenological approach. Thirteen participants were recruited through purposive sampling using the inclusion criteria, such as emergency nurses with more than three years of work experience and nurses who had attended training on effective communication. Data were collected through in-depth interviews with semi-structured questions and analyzed using the Colaizzi’s phenomenological approach. Results: The study generated four themes, namely, the importance of smiles in emergency services, the miracle of smiles, the hindrances for emergency nurses to smile, and that smiles and humor in an emergency situation are important for children. Conclusion: The study concluded that nurses’ smiles had a significant benefit on emergency department services as a form of interpersonal relationship, although the practice still needs to be improved. Nurses are expected to be able to apply smiles in communicating with patients and their families in the emergency departments.